2019
DOI: 10.1186/s12885-019-5475-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SLC2A3 gene and prognosis in colorectal carcinoma: analysis of TCGA data

Abstract: Background Upregulation of SLC2A genes that encode glucose transporter (GLUT) protein is associated with poor prognosis in many cancers. In colorectal cancer, studies reporting the association between overexpression of GLUT and poor clinical outcomes were flawed by small sample sizes or subjective interpretation of immunohistochemical staining. Here, we analyzed mRNA expressions in all 14 SLC2A genes and evaluated the association with prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 26 publications
4
31
2
Order By: Relevance
“…and GLUT2 overexpression has been linked to poor patient outcome [44,96,97]. Interestingly, we found a reduction in GLUT3, as opposed to the ndings in other studies where they have shown upregulation of GLUT3 and its link to poor overall survival [44,96].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…and GLUT2 overexpression has been linked to poor patient outcome [44,96,97]. Interestingly, we found a reduction in GLUT3, as opposed to the ndings in other studies where they have shown upregulation of GLUT3 and its link to poor overall survival [44,96].…”
Section: Discussioncontrasting
confidence: 92%
“…and GLUT2 overexpression has been linked to poor patient outcome [44,96,97]. Interestingly, we found a reduction in GLUT3, as opposed to the ndings in other studies where they have shown upregulation of GLUT3 and its link to poor overall survival [44,96]. Still, research by Younes in 1997 on 289 lung adenocarcinoma samples suggested that GLUT3 overexpression is reported to be mostly found in combination with GLUT1 overexpression as only 21% were positive for both GLUT1 and GLUT3 [98].…”
Section: Discussioncontrasting
confidence: 82%
“…GLUT3 expression is found to be high in non-small cell lung cancer and that correlates to poor prognosis compared to other lung cancer types [31]. In addition, SLC2A3, the gene of GLUT3, is upregulated in high mortality colorectal carcinoma patients based on the TCGA dataset [32]. Additionally, in the brain, GLUT3 is also overexpressed in aggressive brain cancer cells and could impact the drug resistant ability [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Among its 14 members, GLUT1 is broadly expressed in various cancer cells and plays a pivotal role in glycolytic metabolism . Interestingly, a recent report indicates that GLUT3 is also expressed in glioblastoma, colon cancer, and lung cancer, suggesting that GLUT3 also functions in metabolic activity in cancer cells.…”
Section: Introductionmentioning
confidence: 99%